Effect of Intraoperative infusion Magnesium Sulfate Infusion on Postoperative Quality of Recovery in Patients Undergoing Total Knee Arthroplasty: A Prospective, Double-Blind, Randomized Controlled Trial - Xu H; Hao C; Wang X; Du J; Zhang T; Zhang X (Dove Medical Press, 2024)
Hai Xu,1 Conghui Hao,1 Xinxin Wang,2 Jingjing Du,1 Tianyu Zhang,1 Xiaobao Zhang2,3 1Department of Anesthesiology, Graduate Training Base of Lianyungang First People's Hospital of Jinzhou Medical University, Lianyungang, Jiangsu, People's Republic of China; 2Department of Anesthesiology, The Affiliated Lianyungang Hospital of Xuzhou Medical University, Lianyungang, Jiangsu, People's Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital of Kangda College of Nanjing Medical University, Lianyungang, Jiangsu, People's Republic of ChinaCorrespondence: Xiaobao Zhang, Department of Anesthesiology, The First Affiliated Hospital of Kangda College of Nanjing Medical University, Lianyungang, Jiangsu, People's Republic of China, Email hotdog100@163.comBackground: Magnesium sulfate, an intravenous adjuvant, has recently attracted immense attention in multimodal analgesia. Previous studies confirmed the crucial role of magnesium sulfate in postoperative pain and nociceptive hypersensitivity. However, the effect of magnesium sulfate in multimodal analgesia on the quality of recovery (QoR) for elderly patients has not been thoroughly studied. Therefore, the present experiment aimed to investigate the effect of continuous intravenous magnesium sulfate on the quality of postoperative recovery in elderly patients undergoing total knee arthroplasty (TKA).Patients and Methods: In this study, a total of 148 patients scheduled to undergo unilateral total knee arthroplasty were randomized into a magnesium sulfate group (Group M, n=68) and a control group (Group C, n=66) using a double-blind, randomized controlled trial. Before induction of anesthesia, Group M received intravenous magnesium sulfate (40 mg/kg) for 15 min, followed by a continuous infusion (15 mg/kg) until the end of the procedure. In the same manner, Group C received an infusion of the same amount of isotonic saline using the same method as the Group M.Results: Compared with Group C, Group M had significantly better QoR-15 scores on postoperative day 1(POD1) than Group C (P < 0.05). Analysis of the dimensions of QoR-15 scores indicated that Group M exhibited notably reduced levels of pain, and higher levels of emotional state and physical comfort than Group C (P < 0.05). Furthermore, Group C had significantly higher numerical rating scale (NRS) scores at POD1 than Group M (P < 0.05).Conclusion: For elderly patients undergoing knee arthroplasty, magnesium sulfate can be used as an adjuvant in a multimodal analgesic regimen to reduce early postoperative pain and improve the quality of early postoperative recovery.Keywords: magnesium sulfate, quality of recovery, postoperative pain, multimodal analgesic regimen, total knee arthroplasty